NYAI NUR KHODIJAH THE PIONEER OF FEMALE PESANTREN EDUCATION IN INDONESIA - Yusuf Suharto (P3M STAI MIFTAHUL ULUM LUMAJANG, 2023)
KH. Mustofa Bisri referred to Nyai Nur Khadijah as characters who don't not enoughhis services compared to RA Kartini. The difference is, Nyai Nur Khadijah focuses onstrengthening human resource pesantren from among women (female).This combine between alloy references, interviews and traces write and archive still _stored in Ndalem Kasepuhan Pondok Pesantren Mamba'ul Ma'arif Denanyar Jombang. Solong archives in ndalem kasepuhan stored neat and research This is the first with approachanalysis footsteps write combined with references and interviews.Nyai Nur Khodijah is figure woman as the pioneer of female pesantren in Indonesia in1919 in Denanyar Jombang together husband beloved, figure expert fiqh ever became RaisAaam PBNU, KH. Bisri Syansuri.